Analisis Penyebab Stres Kerja Karyawan Yang Berdampak Pada Kinerja Karyawan Pada PT Cube Integrasi Media Jakarta Selatan - Dewistina Laia; Andri Priadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to identify the causes of work stress experienced by employees and its impact on performance at PT Cube Integrasi Media, South Jakarta. The focus of this research is to determine the factors that lead to work stress, understand how stress affects employee productivity and work quality, and find appropriate strategies to overcome it. The research employs a qualitative descriptive method, with data collected through interviews, observations, documentation, and triangulation to ensure data validity. The study involved five employees from various positions within the company.The results indicate that work stress at PT Cube Integrasi Media is caused by several main factors, including excessive workload, tight deadlines, lack of control over work, and technical obstacles within the work system. In addition, the work environment and interpersonal relationships also contribute to increased employee stress levels. The impact of work stress includes reduced concentration, lower productivity, increased work errors, and both physical and mental health problems.Overall, the level of work stress among employees is categorized as high, which negatively affects both individual performance and overall organizational effectiveness. Therefore, it is essential for management to take strategic actions such as fair workload distribution, providing psychological support, and creating a more comfortable and supportive work environment to optimize employee performance.